1984
DOI: 10.1111/j.1365-2125.1984.tb02425.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influence of nifedipine on the pharmacokinetics and pharmacodynamics of propranolol, metoprolol and atenolol.

Abstract: olol 80 mg twice daily, metoprolol 100 mg twice daily and atenolol 100 mg once daily was investigated in eight healthy volunteers. 2 Nifedipine 10 mg three times daily did not affect the pharmacokinetics of metoprolol and atenolol whereas nifedipine shortened the time to peak plasma concentration for propranolol by about 1 h. 3 Propranolol, metoprolol and atenolol provoked comparable decreases in heart rate measured at rest and during exercise. The 13-adrenoceptor blocking properties of propranolol, metoprolol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Combination therapy with calcium-entry blockers, such as dihydropyridines and 1Badrenoceptor blockers, is increasingly used in the management of ischaemic heart disease and hypertension, as it is considered to be more effective than monotherapy with either drug (Hanet etal., 1988;Harris etal., 1982;Lessum et al, 1989;Lynch et al, 1980;Packer, 1989;Pouleur et al, 1984). Calcium-entry blockers, such as nifedipine, have been reported to either increase, decrease, or have no effect on plasma levels of propranolol (Butleir et al, 1984;Gangji et al, 1984;Kleinbloesem et al, 1985). The difficulties the different investigators had in demonstrating significant differences, are due to the small number of subjects in the different studies and the large individual variability of drug levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination therapy with calcium-entry blockers, such as dihydropyridines and 1Badrenoceptor blockers, is increasingly used in the management of ischaemic heart disease and hypertension, as it is considered to be more effective than monotherapy with either drug (Hanet etal., 1988;Harris etal., 1982;Lessum et al, 1989;Lynch et al, 1980;Packer, 1989;Pouleur et al, 1984). Calcium-entry blockers, such as nifedipine, have been reported to either increase, decrease, or have no effect on plasma levels of propranolol (Butleir et al, 1984;Gangji et al, 1984;Kleinbloesem et al, 1985). The difficulties the different investigators had in demonstrating significant differences, are due to the small number of subjects in the different studies and the large individual variability of drug levels.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium-entry blockers, such as nifedipine, have been reported to either increase, decrease, or have no effect on plasma levels of propranolol (Butleir et al, 1984;Gangji et al, 1984;Kleinbloesem et al, 1985). The difficulties the different investigators had in demonstrating significant differences, are due to the small number of subjects in the different studies and the large individual variability of drug levels.…”
Section: Introductionmentioning
confidence: 99%
“…None of these differences is statistically significant. Other studies with multiple doses of nifedipine have shown a significant effect on the disposition of propranolol (but not betaxolol) (Vinceneux et al, 1986) or alternatively no significant effects on the disposition of atenolol, propranolol and metoprolol (Gangji et al, 1984;Kendall et al, 1984), although two of these latter studies again showed higher values for the Cmax of the ,B-adrenoceptor blocker. With felodipine a significant kinetic interaction has been identified with metoprolol (Kendall et al, 1984).…”
Section: Discussionmentioning
confidence: 82%
“…In controlled single and repeated dose trials using therapeutic dosages, nifedipine produced no significant effects on the pharmacokinetics or pharmacodynamics of metoprolol, atenolol or propranolol in healthy volunteers (Elkayam et al 1986;Gangji et al 1984;Kendall et al 1984;Rosenkranz et al 1986). However, in a double-blind, crossover study with healthy volunteers receiving propranolol 80mg every 12h, the addition of nifedipine 10mg 3 times daily increased mean total propranolol Cmax by 56% (p < 0.05) compared with propranolol alone (Vinceneux et al 1986).…”
Section: ;3-adrenergic Blocking Agentsmentioning
confidence: 97%